Students’ Interest towards the Use of Watching Health Movie in Increasing Their English Pronunciation - Fahrul Rizal; Dian Furqani Hamdan; Suyati Suyati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
The problem statement of this thesis what is the students’ interest toward the use of movie in improving pronunciation ability in English Students of IAIN Palopo.  The Objective of the research is to identify the students’ interest in using movie toward the students’ pronunciation ability. This research was a descriptive study. This study was applied after the students followed the pronunciation teaching through watching Health Movies activities. Instrument of the Data Research is questionnaire.  This instrument was given to find out students’ interest in the use of movie. The questionnaire aims to find the students’ interest by using movie. The questionnaire was composed based on ARCS component (Attention, Relevance, Confidence, and satisfaction) and the list construct agree with the researcher’s needs. The questionnaire used Likert Scale. The questionnaire distributed to the respondent after the last treatment of using movie in teaching pronunciation. This research has 10 positive and 10 negative statements. The questionnaire was distributed to the students of experimental group after giving treatment to know their interest toward the implementation of movie in teaching pronunciation.  The questionnaire determined whether the students have positive attitude or not. Based on the result of the questionnaire on the students’ interest, the analysis of questionnaire showed the mean score of students’ interest was 89.4 or equivalent to strongly positive classification. This leads to the conclusion that the use of movie can increase the interests of the English students at IAIN Palopo in learning pronunciation .